Methane pumping by rapidly refreezing lead ice in the ice-covered Arctic Ocean - Damm, Ellen; Thoms, Silke; Angelopoulos, Michael; Von Albedyll, Luisa; Rinke, Annette; Haas, Christian (Frontiers in Earth Science, 2024)
If and how the sea ice cycle drives the methane cycle in the Arctic is an open question and crucial to improve source/ sink balances. This study presents new insights into the effects of strong and fast freeze on the physical-chemical properties of ice and implications for methane fluxes into and out of newly formed lead ice. During the transpolar drift MOSAiC 2019-2020 we took weekly samples of growing lead ice and underlying seawater at the same site, between January and March 2020. Based on this time series we analyzed concentrations and stable carbon isotopic signatures ( 13 -C-CH4) of methane and calculated methane solubility capacities (MSC) and saturation levels in both environments.During the first month intense cooling resulted in the growth of two thirds of the final ice thickness. In the second month, ice growth speed decreased by 50%. Both growth phases, disentangled, exposed different freeze impacts on methane pathways. Fast freeze caused strong brine entrapment keeping the newly formed lead ice permeable for two weeks. These physical conditions activated a methane pump: An increased MSC induced methane uptake at the air-ice interface and the still open brine channels a top-down transport to the ice-ocean interface with brine drainage. When the subsurface layer became impermeable, the top-down pumping stopped but the still ongoing uptake induced a methane excess on top. During the second growth phase, methane exchange exclusively continued at the ice-ocean interface. The shift in the relative abundance of the 12 C and 13 C isotopes between lead ice and seawater towards a 13 C-enrichment in seawater reveals brine drainage as the main pathway releasing methane from aging lead ice.We conclude that in winter refrozen leads temporarily function as sinks for atmospheric methane and postulate that the relevance of this process may even increase when the Arctic fully transitions into a seasonally ice-covered ocean when leads may be more abundant. To highlight the large scale relevance of methane in-gassing at the air-ice interface as potential but still unconsidered pathway, we include estimates of the occurrence and frequency of young lead ice from satellite observations of leads during MOSAiC.